The Educational Axiology of Al-Maqbul Traditional Pesantren - Sulton, Ahmad (Analisa: Journal of Social Science and Religion, 2023)
This study is prompted by criticism to the educational activities undertaken by Islamic educational institutions for adopting Western educational axiology. On the contrary, as a reputable school, Pesantren Al-Maqbul refuses to make transformation into a modern one, and still preserves the traditional education system. This study aims to explore the reasons Pesantren Al-Maqbul maintains the traditional education system with perspective of educational axiology. This study answers the research qustions about what are the ethical and aesthetic values at the Pesantren Al-Maqbul?, and what are the education purposes at the Pesantren Al-Maqbul?. This study uses a qualitative approach that seeks to describe data from the field and literature related to the axiology of traditional pesantren education. Observation, interview and documentation techniques were used to obtain data related to the discussion, which were then analyzed. This research resulted in findings, namely: (1) The reasons for the Pesantren Al-Maqbul to maintain the traditional education system cannot be separated from the axiological construction of its education; (2) The influence of the axiological basis of education can be identified from the tendency of normative values, namely being bound by Islamic provisions in the aesthetics of education at Pesantren Al-Maqbul; (3) The tendency of akhlāq at-Ṭā'ah (obedience ethics) and akhlāq al-Fanā' (illuminative ethics) is found in educational ethics at Pesantren Al-Maqbul; (4) The aim of education at the Pesantren Al-Maqbul is to study Islamic religious knowledge (tafaqquh fi al-din). There is no space for general knowledge (science) to be studied at the Pesantren Al-Maqbul.